Screening of Luzula species native to the Carpathian Basin for anti-inflammatory activity and bioactivity-guided isolation of compounds from Luzula luzuloides (Lam.) Dandy & Wilmott - Tóth Barbara; Chang Fang-Rong; Hwang Tsong-Long; Szappanos Ádám; Mándi Attila; Hunyadi Attila; Kurtán Tibor; Jakab Gusztáv; Hohmann Judit; Vasas Andrea (2017)
Abstract The present study focused on the anti-inflammatory screening of Luzula species native to the Carpathian Basin and bioactivity-guided isolation of compounds of Luzula luzuloides (Lam.) Dandy & Wilmott. The anti-inflammatory properties of extracts with different polarity prepared from Luzula species were determined. Among them, the CH2Cl2-soluble fraction of L. luzuloides possessed strong inhibitory effects on superoxide anion generation (99.39 ± 0.37%) and elastase release (114.22 ± 3.13%) in fMLP/CB-induced human neutrophils at concentration of 10 μg/mL. From this fraction, six compounds (1–6) were isolated by the combination of different chromatographic methods. The structures of the compounds were determined by means of MS, 1D and 2D NMR spectroscopy. The results allowed the identification of the new 1,6-dihydroxy-2-keto-1,7-dimethyl-8-vinyl-1,2-dihydrophenanthrene (1) from the plant, named luzulin A. Chiral HPLC and HPLC-ECD analysis revealed that 1 possesses low enantiomeric excess and TDDFT-ECD calculations afforded the configurational assignment of the separated enantiomers. Three known phenanthrenes [juncuenin B (2), dehydrojuncuenin B (3) and juncusol (4)] and two flavonoids [apigenin (5) and luteolin (6)] were also isolated. The anti-inflammatory activity of the isolated compounds was tested and IC50 values were determined. This was the first time that phenanthrenes were detected in a Luzula species. The oxidative transformation of juncuenin B (3) led to the isolation of its possible biometabolites, namely luzulin A (1), dehydrojuncuenin B (4), and juncuenin D (7). The isolated compounds (1–4) confirm that besides flavonoids, phenanthrenes could also serve as chemotaxonomic markers for Luzula species and prove the close relationship of Juncus and Luzula genus.